Implementasi Sigalovadasutta dalam Tradisi Nyadran Dauwang sebagai Wujud Bakti Leluhur oleh Masyarakat Buddha Dusun Depok - Rosalina Desi Paramita (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the implementation of the Sigalovada Sutta as a form of ancestral devotion within the Nyadran Dauwang tradition practiced by the Buddhist community in Depok Hamlet, Java. Grounded in the understanding that religion and culture are deeply intertwined, the research aims to explore how Buddhist doctrinal values are actualized through local communal rituals and how these practices contribute to social cohesion, environmental stewardship, and cultural continuity. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews with religious leaders, elders, and community members, and analysis of ritual documentation. Triangulation of methods and sources was applied to enhance the credibility and depth of interpretation. The findings reveal that Nyadran Dauwang consists of four interrelated components: communal cleaning of irrigation canals (Susuk Wangang), ritual journeys accompanied by offerings and food sharing, interfaith prayer gatherings, and Wayang Kulit performances. These practices embody key Buddhist values such as spiritual friendship, loving-kindness, compassion, ethical reciprocity, and collective merit-making, as articulated in the Sigalovada Sutta. The tradition also reinforces respect for ancestors, strengthens intergenerational bonds, promotes ecological awareness, and fosters harmony in a pluralistic religious setting. Rather than functioning as a rigid doctrinal text, the Sigalovada Sutta operates as a living ethical framework that guides communal life through culturally resonant forms. In conclusion, the study demonstrates that Nyadran Dauwang represents a contextualized enactment of Buddhist ethics that integrates religious teachings with local cultural heritage. This integration offers an important model for Buddhist religious education, cultural preservation, and community-based approaches to social and environmental sustainability.